Action distance as a predictor of winning and losing matches at FIVB Volleyball Men`s World Championship - Mroczek D.; Pawlik, D. (Baltic Journal of Health and Physical Activity, 2023)
Introduction: Technology determines the emergence of functional tools to monitor and control motor activity during the game. One of the solutions for monitoring the player in indoor sports are computer video analyses, which determine basic kinematic parameters. The study aims to compare team and player activity with the outcome of a given set and the effect of the game status on player activity during a championship-level match.